2018
DOI: 10.1055/s-0038-1666864
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Characterisation of Traditional Homeopathically Manufactured Cuprum metallicum and Gelsemium sempervirens Medicines and Controls

Abstract: Potentisation influences specifically the nature of NPs detected. This material demonstrates that the step-by-step process (dynamised or not) does not match with the theoretical expectations in a dilution process. The Avogadro/Loschmidt limit is not relevant at all. It was not possible to reproduce the findings of Chikramane et al (2010) using inductively coupled plasma-mass spectrometry with copper. Copper NPs could not be detected at 4cH and above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Upadhyay (2018aUpadhyay ( , 2018b explained further that the presence of sourcedrug in high potency medicine is not possible except as impurity or by contamination. Investigating self-made test samples, Van Wassenhoven et al (2018) could not validate the findings of Chikramane et al (2010). Upadhyay (2017Upadhyay ( , 2018aUpadhyay ( , 2018b explained that to understand homeopathic medicine, one would have to abandon the materialistic view that the physical presence of its source-drug is necessary for therapeutic effects.…”
Section: New Scientific Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Upadhyay (2018aUpadhyay ( , 2018b explained further that the presence of sourcedrug in high potency medicine is not possible except as impurity or by contamination. Investigating self-made test samples, Van Wassenhoven et al (2018) could not validate the findings of Chikramane et al (2010). Upadhyay (2017Upadhyay ( , 2018aUpadhyay ( , 2018b explained that to understand homeopathic medicine, one would have to abandon the materialistic view that the physical presence of its source-drug is necessary for therapeutic effects.…”
Section: New Scientific Understandingmentioning
confidence: 99%
“…2. High potency homeopathic medicines supposedly do not contain any molecules of the source-drug (Upadhyay, 2018a;Upadhyay, 2018b;Van Wassenhoven et al, 2018) but reported to cause hormetic activation (Chikramane et al, 2017).…”
Section: Hormesis and Ultramolecular Dilutionmentioning
confidence: 99%
“…The goals of this paper are to analyze the relations and to propose an experimental technique that has the potential of revealing these relations. These goals are important, because SDVSASs are relevant for toxicology, medicine, wastewater treatment and power generation (Konovalov et al, 2014;Ryzhkina et al, 2011;van Wassenhoven et al 2017van Wassenhoven et al , 2018Bandyopadhyay et al, 2017). To pursue these goals, firstly, I summarize the facets of the empirical and the quantum electrodynamic (QED) models of SDVSASs, i.e., only those facets required for analyzing the abovementioned relations.…”
Section: Introductionmentioning
confidence: 99%